Zika virus has an oncolytic activity against human glioblastoma U87 cells - V. A. Svyatchenko; I. A. Razumov; E. V. Protopopova; A. V. Demina; O. I. Solovieva; E. L. Zavjalov; V. B. Loktev (Вавиловский журнал генетики и селекции)
Glioblastoma is a highly lethal brain cancer. Virotherapy with the use of oncolytic viruses has since recently been regarded as a promising approach for the clinic treatment of human glioblastomas. The purpose of this work was to perform a primary evaluation of the Zika virus as a potential oncolytic agent against glioblastomas. In vitro experiments showed that the Zika virus strain MR 766 is able to selectively infect and lyse neoplastic cells of the human glioblastoma cell line U87 MG. The selectivity index (SI, the ratio of infectious titer for tumor cells to titer on normal untransformed cells) was 2·102. The selectivity of the replicative activity of Zika virus in relation to U87 MG glioblastoma cells was additionally confrmed by indirect immunoﬂuorescence. Using the model of immunodefcient SCID mice with subcutaneous xenografts of human glioblastoma U87 MG, a strong antitumor activity of the Zika virus under a course (daily for 4 days) of intratumoral administration of 5·105 TCID50 of Zika virus was shown. Treatment with Zika virus resulted in more than a 10fold reduction in mean volumes of tumors. The tumor growth inhibition index was 92.63 %. Recurrences (metastases) of tumor regrowth were not registered within 64 days of observation. This result demonstrated the prospect of further indepth studies of the Zika virus as a potential oncolytic agent against human glioblastomas.